Conflicts due to the use of agrochemicals: the role of rural women in Uruguay - Chiappe, Marta (Agrociencia Uruguay, 2020)
Since the end of the 2000s, Uruguay registered a strong process of transformation in the agricultural sector, mainly due to the expansion in the area of ​​soybean cultivation. This process was accompanied by a substantial increase in the use of agrochemicals (fertilizers, herbicides and insecticides), an unprecedented phenomenon in the country in terms of scale. In parallel, complaints of intoxication have grown strongly, both by urban and rural residents. The objective of this work is to investigate the role that women have had in denouncing the effects of the application of agrochemicals and the way they perceive they have affected them, their families and communities. The study included a review of press articles and documents referring to cases in which women were protagonists of the complaints, and interviews with qualified informants and women complainants. From the information collected it is possible to conclude, on the one hand, that the complaints have contributed to evidence the consequences of agrochemical applications, and on the other hand, to break with the traditional invisibility of women in the rural context and generate new frameworks in the social relations of the affected areas. However, it was also detected that there are still social and cultural barriers that inhibit women from making complaints and threaten the visibility of problems affecting rural communities.